A study on the level of adherence of the UP Diliman Main Library Virtual reference services to the RUSA guidelines for implementing and maintaining VRS - Labiano, Faye F. (2014)
The purpose of the study is to determine the level of adherence of the virtual reference services of the UP Diliman Main Library to the RUSA Guidelines for Implementing Virtual Reference Services (Ask-a-librarian, e-mail, Facebook fan page) from the perspective of the library staff themselves. The study focused in four key areas - preparation for offering the service, provision of service, organization of service, and privacy of users. Survey and interview were conducted among the reference librarians of the aforementioned institution. Concepts of averages and percentages were applied to analyze and interpret data. Areas scoring less than or equal to 40% are considered to have very low level of adherence. Those that gathered 41 - 50% are classified under low level of adherence. Meanwhile, areas rendering 51 - 60% are said to have high level of adherence. Those that scored greater than or equal to 61% are considered to have very high level of adherence. The findings of the study reveal that the virtual reference services of said institution have: 1.) high level of adherence (75%) to preparation for offering the service guidelines, 2) low level of adherence (55%) to provision of service guidelines, 3) very low adherence (17%) to organization of service guidelines, 4) low level of adherence (50%) to ensuring privacy of users. Based on these findings, it can be concluded that from the perspective of the library staff, the virtual reference services of the UP Diliman Main Library has an overall low level of adherence (49%) to the RUSA Guidelines for Implementing and Maintaining VRS.